Anode supported planar solid oxide fuel cells with the large size of 30 cm × 30 cm via tape-casting and co-sintering technique. (21st January 2016) - Xue, Yejian; Guan, Wanbing; He, Changrong; Liu, Wu; Wang, Jianxin; Sun, Shanshan; Wang, Zhenwei; Wang, Weiguo
Abstract: In this work, the NiO−8YSZ/8YSZ half-cells for planar ASCs with the large size of 30 cm × 30 cm are prepared by optimizing both the sintering characteristics and the sintering temperature. The shrinkage rates, open porosities and flexural strength of the half-cells are investigated systematically. The large size half-cells which are prepared by the tape-casting, co-sintering and two-step sintering method show the optimal comprehensive performances with the sintering temperature being 1350 °C. The NiO+8YSZ/8YSZ/LSM+8YSZ anode-supported single cells are obtained at the sintering temperature of 1050 °C. The maximum measurement power at output voltage of 0.8 V of the two cells and 1.6 V of the stack can reach 32.6 W, 34.7 W and 67.3 W, respectively. The two-cells stack is successively discharged under constant current of 5 A for 316 h with the degradation rate of 1.58% kh −1 and 30 A for 1161 h with no degradation at the temperature of 750 °C. The large size ASCs show the good mechanical strength and an acceptable degradation. Highlights: The planar ASCs with the size of 30 cm × 30 cm were prepared. The measurement Pmax of the two-cell short stack could reach 67.3 W at 750 °C. The stack showed an acceptable degradation under constant current discharge.